Motivasi Belajar Ipa Siswa Kelas VII SMP Penda Tawangmangu Tahun Pelajaran 2013/2014 - Nofianingsih, Fajar Ika; , Drs. Djumadi, M.Kes (2014)
In the all of education process which happened in school, study is the most important activity (Slameto, 2003). Student have many factor influence or their result of study and achievement. The purpose of this research to know the students' motivation to learn science VII for grade Junior High School Penda Tawangmangu academic year of 2013/2014. Kind o this research is descriptive with a qualitative approach. The location of this research is in Junior High School Penda Tawangmangu. We use observation and questionnaire as a data source. The result of data source from 32 sample with simple random sampling technique to determine the students' motivation to learn science class VII Junior High School Penda Tawangmangu academic year of 2013/2014. From triangulation technique to analysis data we found basic of research. Result is 23 (71,875%) students who interested whit examination, 20 (62,5%) try to finished the difficulty. From 30 (93,75%) students more like working by them self. There are 24 (75%) active students and 23 (71,875%) enthusiastic students. This conclusions is all of the student should have a motivation to study. For the purpose of study can research.